Importance of base-pair opening for mismatch recognition - Bouchal, Tomáš; Durník, Ivo; Illík, Viktor; Réblová, Kamila; Kulhánek, Petr (Nucleic acids research, 2020)
Mismatch repair is a highly conserved cellular pathway responsible for repairing mismatched dsDNA. Errors are detected by the MutS enzyme, which most likely senses altered mechanical property of damaged dsDNA rather than a specific molecular pattern. While the curved shape of dsDNA in crystallographic MutS/DNA structures suggests the role of DNA bending, the theoretical support is not fully convincing. Here, we present a computational study focused on a base-pair opening into the minor groove, a specific base-pair motion observed upon interaction with MutS. Propensities for the opening were evaluated in terms of two base-pair parameters: Opening and Shear. We tested all possible base pairs in anti/anti, anti/syn and syn/anti orientations and found clear discrimination between mismatches and canonical base-pairs only for the opening into the minor groove. Besides, the discrimination gap was also confirmed in hotspot and coldspot sequences, indicating that the opening could play a more significant role in the mismatch recognition than previously recognized. Our findings can be helpful for a better understanding of sequence-dependent mutability. Further, detailed structural characterization of mismatches can serve for designing anti-cancer drugs targeting mismatched base pairs.
Keywords: DNA; DNA Mismatch Repair; výpočetní biologie; termodynamika; Molecular Dynamics Simulation; simulace molekulární dynamiky; oprava chybného párování bází DNA; vazebný protein MutS opravné syntézy DNA; Base Pair Mismatch; párování bází; vodíková vazba; Hydrogen Bonding; Base Pairing; Computational Biology; Thermodynamics; chybné párování bází; MutS DNA Mismatch-Binding Protein